Dopamine D1 receptors in the anterior cingulate cortex regulate effort-based decision making. - Schweimer, J; Hauber, W (2006)
The anterior cingulate cortex (ACC) has been implicated in encoding whether or not an action is worth performing in view of the expected benefit and the cost of performing the action. Dopamine input to the ACC may be critical for this form of effort-based decision making; however, the role of distinct ACC dopamine receptors is yet unknown. Therefore, we examined in rats the effects of an intra-ACC D1 and D2 receptor blockade on effort-based decision making tested in a T-maze cost-benefit task. In this task, subjects could either choose to climb a barrier to obtain a high reward in one arm or a low reward in the other arm without a barrier. Unlike vehicle-treated rats, rats with intra-ACC infusion of the D1 receptor antagonist SCH23390 exhibited a reduced preference for the high-cost- high-reward response option when having the choice to obtain a low reward with little effort. In contrast, in rats with intra-ACC infusion of the D2 receptor antagonist eticlopride, the preference for the high-cost-high-reward response option was not altered relative to vehicle-treated rats. These data provide the first evidence that D1 receptors in the ACC regulate effort-based decision making.